MAP OF THE WORLD : an introduction to mathematical geodesy. - Vermeer, Martin ([Place of publication not identified] : CRC PRESS, 2019)
The development of mathematical theory, together with its implementation and use, needed to process, analyze, integrate and validate geodetic data, such as measurements for landsurveying, is referred to as the discipline of Mathematical Geodesy. It is about the calculus of observation, the validation of measurements and mathematical models, and the analysis of spatial and temporal phenomena in geosciences, i.e. about parameter estimation, testing and reliability, and about interpolation and prediction. Map of the World: An Introduction to Mathematical Geodesy aims to provide an accessible introduction to this area, presenting the most pertinent mathematical foundations relating to maps, mapping and the production of geospatial data. FeaturesWritten in a fluid and accessible style, replete with exercises; ideal for undergraduate courses Suitable for students of land surveying and natural science, as well as professionals, but also for map amateurs
OCLC-licensed vendor bibliographic record.
Keywords: Geodesy -- Mathematics; MATHEMATICS / General